TRANSFORMATIONAL LEADERSHIP, WORK DISCIPLINE, AND ORGANIZATIONAL COMMITMENT'S INFLUENCE ON EMPLOYEE PERFORMANCE - Darmawati Manda; Andi Tenry Sose; Faridah Faridah; Lukman Lukman (Brilliant International Journal Of Management And Tourism, 2023)
The study's goal is to look into the effects of transformational leadership, work discipline, and organizational commitment on employee performance at the West Java Preservation Hall. The participants in this study were employees of the West Java Conservation Center. With 73 respondents, we used the Slovin formula and a stratified random sampling technique. Data analysis techniques based on traditional assumption testing include the normality and heteroscedasticity tests. Hypothesis testing with the T test, F test, coefficient of determination R2, and beta coefficient of standardization. The results showed that transformational leadership had a positive significant effect on employee performance, work discipline had a positive significant effect on employee performance, and the presence of organizational commitment had a positive significant effect on employee performance at the West Java Conservation Center. Concurrently, transformational leadership, work discipline, and organizational commitment all had a significant impact on employee performance.